Risk Aversion, Insurance, and the Efficiency-Equality Tradeoff - Samuel Bowles; Herbert Gintis (University of Massachusetts, Department of Economics, 2000)
Under conditions of informational asymmetry, redistributing the property rights may improve work incentives but lead to an inefficient choice of entrepreneurial risk. We present a model in which reassignment of property rights does not affect factor prices and we show that there exist egalitarian asset redistributions that enhance allocative efficiency. The scope for such redistributions can be broadened by offering fair insurance protecting the independent entrepreneur against risk unassociated with the production process and against production uncertainties that are unrelated to the quality of their individual decisions. The market will generally supply insurance of this type suboptimally.
Keywords: 330